1997
DOI: 10.1046/j.1365-2036.1997.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

A United States multicentre trial of dual and proton pump inhibitor‐based triple therapies for Helicobacter pylori

Abstract: Background: One‐week proton pump inhibitor‐based triple therapies are very popular in the US despite limited US data documenting efficacy. We assessed 1‐week proton pump inhibitor triple therapies for Helicobacter pylori, and compared them to dual antibiotic therapies (to assess benefit of omeprazole) and to omeprazole–amoxycillin (to assess benefit of clarithro‐ mycin) in a large, randomized, US multicentre study. Methods: Healthy subjects who were H. pylori‐positive by rapid serological test and 13C‐urea bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 5 publications
2
47
0
Order By: Relevance
“…As shown in figure 2, treatment success fails to reach even 80% in most studies in the southern and central European countries of France, Italy, Spain and Turkey, populations which, as the Maastricht III report noted, tend to have a high prevalence (∼18.5%) of clarithromycin resistance (figure 2). Similar poor results were obtained in the more recent large US trials of triple regimens 68 77 89–91. Using meta-regression methods described previously,7 92 we observed treatment success for the more commonly used ‘legacy triple therapy’ to be ∼8.1% lower than treatment success for the combination using metronidazole in place of amoxicillin in recent years (95% CI 2.2% to 14.0%).…”
Section: The Current Status Of Clarithromycin-containing Triple Regimenssupporting
confidence: 79%
“…As shown in figure 2, treatment success fails to reach even 80% in most studies in the southern and central European countries of France, Italy, Spain and Turkey, populations which, as the Maastricht III report noted, tend to have a high prevalence (∼18.5%) of clarithromycin resistance (figure 2). Similar poor results were obtained in the more recent large US trials of triple regimens 68 77 89–91. Using meta-regression methods described previously,7 92 we observed treatment success for the more commonly used ‘legacy triple therapy’ to be ∼8.1% lower than treatment success for the combination using metronidazole in place of amoxicillin in recent years (95% CI 2.2% to 14.0%).…”
Section: The Current Status Of Clarithromycin-containing Triple Regimenssupporting
confidence: 79%
“…Triple therapies are the mainstay of current treatment but resistance to clarithromycin is reducing its effectiveness. In the presence of resistance to clarithromycin, some studies have shown eradication rate below 80% and even as low as 25%-61% with standard triple therapy containing clarithromycin, amoxycillin and a proton-pump inhibitor [7][8][9][10][11] . Clarithromycin resistance is also increasing in our region [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous large European trials have reported an eradication rate with one-week triple therapy of >85% [44,46]. Unfortunately, currently available studies conducted in the United States have not reproduced the encouraging observations made in Europe [29,47]. As such, the report of the recent Digestive Health Initiative International Update Conference on Helicobacter pylori recently recommended that therapy be given for 14 days in the United States [43].…”
Section: Factors Influencing the Effectiveness Of Therapymentioning
confidence: 97%
“…Side effects are most often associated with clarithromycin. They include altered taste, nau- [29,30]. PPI or RBC-based triple therapies (Table 2) are effective in eradicating H. pylori infection, and are reasonably well tolerated by patients [31].…”
Section: Opinion Statementmentioning
confidence: 99%